Kinetic modeling of essential oil hydro-distillation from peels of pomelo (Citrus grandis L.) fruit grown in Southern Vietnam - Tan, Phat Dao; Huynh, Xuan Phong; Huynh, Mai Chang; Long, Giang Bach; Nguyen, Van Muoi (Penerbit Universiti Kebangsaan Malaysia, 2021)
Thorough understanding of kinetics plays a key role in improving existing industrial processes. In this study, we attempted to model the kinetics of the hydro-distillation process that produces essential oil from peels of pomelo (Citrus grandis L.) fruit, which is a product with high economic value and a wide range of applications. We first determined the optimal water-to-material ratio for attaining maximal oil yield. Then, further experimental attempts were carried out at different distillation rates to generate experimental data to fit three kinetic models, namely first-order kinetics model, instantaneous washing, followed by diffusion model and simultaneous washing and diffusion model. Overall, the three models have well described the experimental kinetic data on hydro-distillation (R2> 90%). Of which, the simultaneous washing and diffusion model attaining the R2 of 99.97% was chosen as the most suitable to describe the kinetics of the extraction process. Estimated parameters also shown that the washing stage occurs more rapidly than the later, diffusion stage. GC-MS results showed that the obtained oil sample was characterized by the dominance of the D-Limonene compound (97.873%).